Simultaneous determination of ascorbic acid and free malondialdehyde on human serum by HPLC-UV - Karatepe, M (Mjh Life Sciences, 2004)
Ascorbic acid and malondialdehyde levels are two important parameters for the measurement of oxidative stress in biological systems. Ascorbic acid is an important antioxidant from dietary sources. Malondialdehyde, one of the major secondary oxidation products of peroxidized polyunsaturated fatty acids, has been shown to be of biological significance. A new method for measurement of ascorbic acid and malondialdehyde was tested with the same analysis conditions in human serum from diabetic patients and healthy individuals. Ascorbic acid and malondialdehyde levels of patients with diabetes mellitus were significantly different from the controls. The detection limits for ascorbic acid and malondialdehyde were 1.3 X 10(-8) mol/L and 1.02 X 10(-8) mol/L, respectively. This simple, rapid, and sensitive method is useful for clinical measurements.
Keywords: Performance Liquid-Chromatography; Plasma Malondialdehyde; Dehydroascorbic Acid; Vitamin-C; Antioxidants; Stress